Education for village ambulance drivers in patient evacuation - Sodiq Kamal; Yeni Lusiyati; Judi Andriwanto; Tomy Sri Wardani Purnomo; Arifin Syam (Community Empowerment, 2023)
In order to support community health services, the Bandongan subdistrict government has provided each village with an ambulance unit. The available human resources, however, fall short in many ways. For this reason, the PPMT Unimma team is interested in educating village ambulance drivers so that their abilities can be improved. In cooperation with the Police Traffic Unit and Tidar Hospital, training and simulation are the method used to address this issue. As a result of this program, ambulance drivers now have more knowledge and expertise to evacuate the emergency patients.